Factors associated with participation and completion of a survey-based study: Analysis of work conditions and quality improvement in primary care. Issue 8 (8th October 2018) - Yale, Steven H.; Liang, Hong; Schmelzer, John R.; Poplau, Sara; Bell, Lauren Nicole; Toklu, Hale Z.; Brown, Roger L.; Williams, Eric; Linzer, Mark
Abstract : Purpose: The Healthy Work Place (HWP) study investigated methods to improve clinicians' dissatisfaction and burnout. The purpose of this paper is to identify factors that influenced study enrollment and completion and assess effects of initial clinic site enrollment rates on clinician outcomes, including satisfaction, burnout, stress and intent to leave practice. Design/methodology/approach: In total, 144 primary care clinicians (general internists, family physicians, nurse practitioners and physician assistants) at 14 primary care clinics were analyzed. Findings: In total, 72 clinicians enrolled in the study and completed the first survey (50 percent enrollment rate). Of these, 10 did not complete the second survey (86 percent completion rate). Gender, type, burnout, stress and intervention did not significantly affect survey completion. Hence, widespread agreement about most moral/ethical issues (72 percent vs 22 percent; p =0.0060) and general agreement on treatment methods (81 percent vs 50 percent; p =0.0490) were reported by providers that completed both surveys as opposed to just the initial survey. Providers with high initial clinic site enrollment rates (=50 percent providers) obtained better outcomes, including improvements in or no worsening of satisfaction (odds ratio (OR)=19.16; p =0.0217) and burnout (OR=6.24; p =0.0418). Social implications: More providers experiencing workplace agreement completed the initial and final surveys, and providers at sites with higher initial enrollment rates obtained better outcomes including a higher rate of improvement or no worsening of job satisfaction and burnout. Originality/value: There is limited research on clinicians' workplace and other factors that influence their participation in survey-based studies. The findings help us to understand how these factors may affect quality of data collecting and outcome. Thus, the study provides us insight for improvement of quality in primary care.